2023
DOI: 10.1097/shk.0000000000002175
|View full text |Cite
|
Sign up to set email alerts
|

Utility of sTREM-1 biomarker and hcp Gene for Identification of Acinetobacter baumannii Colonization and Infection in Lung

Abstract: Objective Respiratory infections or colonization of Acinetobacter baumannii (Ab) are common in clinical practice but are treated differently. Early identification of Ab infection and colonization reduces the risk of antibiotic mismatch but objective laboratory indicators to distinguish between bacterial infections and colonization are lacking. To distinguish infection and colonization of Ab, we tested the role of two biomarkers, triggering receptor expressed on myeloid cells-1 (TREM-1) and Hemolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…23,24 Research has shown that TREM-1 expression can be induced by various viral infections, including influenza A virus and hepatitis C virus, as well as bacterial infections like Staphylococcus aureus and Pseudomonas aeruginosa. [25][26][27] Soluble TREM-1 (sTREM-1) is a 27 kDa peptide composed of the extracellular domain of TREM-1, which can be shed into the bloodstream. 28,29 Multiple studies have investigated the use of sTREM-1 for predicting mortality in sepsis patients.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Research has shown that TREM-1 expression can be induced by various viral infections, including influenza A virus and hepatitis C virus, as well as bacterial infections like Staphylococcus aureus and Pseudomonas aeruginosa. [25][26][27] Soluble TREM-1 (sTREM-1) is a 27 kDa peptide composed of the extracellular domain of TREM-1, which can be shed into the bloodstream. 28,29 Multiple studies have investigated the use of sTREM-1 for predicting mortality in sepsis patients.…”
Section: Introductionmentioning
confidence: 99%